Influence of Receivables Turnover and Inventory Turnover to Profitability PT Kimia Farma (Persero) Tbk - Novita Wulandari; Iman Lubis (YPPP AL-AMSI, 2021)
This study aims to determine the effect of receivables turnover (RTO) and inventory turnover (ITR) on profitability (ROA). The method used in this study is a quantitative method by taking the financial statements of PT Kimia Farma (Persero) Tbk. This study uses descriptive statistical analysis, classical assumption test, predictive multiple regression predictive hypothesis testing and coefficient of determination with SPSS Version 22 software. Receivable Turnover (RTO) partially has no a significant effect where tcount 1.166 < ttable 2.44691 with a significant value of 0.288 > 0.05 on profitability (ROA) and Inventory Turnover (ITR) partially has no a significant effect where tcount 0.149 < ttable 2.44691 with a significant value of 0.887 > 0.05 on profitability (ROA). Simultaneously, Accounts Receivable and Inventory Turnover have no effect where Fcount 1.563 < Ftable 5.14 with a significant level of 0.284 > 0.05.